Updated review of advances in microRNAs and complex diseases: towards systematic evaluation of computational models. Issue 6 (23rd September 2022) - Huang, Li; Zhang, Li; Chen, Xing
Abstract: Currently, there exist no generally accepted strategies of evaluating computational models for microRNA-disease associations (MDAs). Though K -fold cross validations and case studies seem to be must-have procedures, the value of K, the evaluation metrics, and the choice of query diseases as well as the inclusion of other procedures (such as parameter sensitivity tests, ablation studies and computational cost reports) are all determined on a case-by-case basis and depending on the researchers' choices. In the current review, we include a comprehensive analysis on how 29 state-of-the-art models for predicting MDAs were evaluated. Based on the analytical results, we recommend a feasible evaluation workflow that would suit any future model to facilitate fair and systematic assessment of predictive performance.